Impact of HS on work loss, indirect costs and income. (1st July 2019) - Tzellos, T.; Yang, H.; Mu, F.; Calimlim, B.; Signorovitch, J.
Summary: Hidradenitis suppurativa (HS) is a rare, long‐term skin disease that causes painful lumps under the skin. HS affects between 0.1% and 4% of the population of the U.S., where this study took place, and the symptoms can interfere with daily life and ability to work. HS often begins between puberty and the age of 40, so many people with HS are in their prime working years. This study aimed to find out how the work life of people with HS was impacted compared to similar people without HS. The authors used a database of insurance claims to find employed people with HS and without HS (controls) who were between 18 and 64 years old. The authors found that people with HS had lower annual income, more missed days at work, and higher costs related to missed work days and disability than people without HS. In addition, people with newly diagnosed HS had a slower increase in income and were more likely to leave their job than those without it, over 5 years following the diagnosis. In conclusion, HS can negatively affect a person's work life and income earning, suggesting that better therapies are needed to help manage the disease symptoms and improve the lives of people with HS. Abstract : Linked Article:  Tzellos et al. Br J Dermatol 2019; 181 :147–154